Tinjauan Yuridis POJK Nomor 65/POJK.03/2016 tentang Mitigasi Risiko Perbankan Syariah Analisis Yuridis terhadap Penerapan Manajemen Risiko pada Bank Umum Syariah di Indonesia - Zahwa Khoirunnisa; Debi Larasati; Fakhry Fadhil (Al Barakat, 2026)
Risk management in Islamic banking is an important process to maintain the stability and sustainability of Islamic financial institutions. Islamic banks operate based on Sharia principles, such as profit-sharing and the prohibition of riba, gharar, and maisir, which create unique risk characteristics compared to conventional banks. This study discusses the implementation of risk management in Islamic banking based on Law Number 21 of 2008 and POJK Number 65/POJK.03/2016. The discussion includes the stages of risk management: risk identification, measurement, monitoring, and control, as well as the ten types of risks that must be managed by Islamic banks. The study concludes that effective risk management is essential to ensure prudential banking practices, maintain public trust, and support the growth of a stable and competitive Islamic banking system.